Współpraca transgraniczna pomiędzy Unią Europejską i krajami sąsiedzkimi Europy Wschodniej w ramach Europejskiej Polityki Sąsiedztwa - Kalicka-Mikołajczyk, Adriana (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
The European Neighbourhood Policy (ENP) was developed in 2004, with the objective of avoiding the emergence of new dividing lines between the enlarged EU and its neighbours and strengthening the prosperity, stability and security of all. It is based on the values of democracy, rule of law and respect of human rights. Under the ENP, the European Union works together with its partners to develop democratic, socially equitable and inclusive societies, and offers its neighbours economic integration, improved circulation of people across borders, financial assistance and technical cooperation toward approximation with European Union standards. The ENP also offers to its partners a very concrete set of opportunities through its sector policies. These cover a broad range of issues, reaching from employment and social policy, trade, industrial and competition policy to agriculture and rural development, climate change and environment. They include energy security, transport, research and innovation, as well as support to health, education, culture and youth. Cross-border cooperation is a key element of the EU policy towards its neighbours within the framework of the ENP because its supports sustainable development along the EU’s external borders, helps reducing differences in living standards and addressing common challenges across these borders. However, the specific objectives of this very important area of mutual cooperation are to promote a coherent and integrated approach to regional development, dealing with common challenges, guaranteeing effectiveness and security at the external borders and to encourage local cooperation.
Keywords: European Neighbourhood Policy; European Neighbourhood Instrument; cross-border cooperation programmes; European Union; cross-border cooperation